Cold Fission. - Samuel K. Moore (IEEE spectrum)
Global Technologies is working on a nuclear voltaic cell consisting basically of a semiconductor and an amount of radioactive material. By replacing solid semiconductors with molten selenium and molten sulfur, GT's nuclear battery could run on much more powerful radiation than a beta cell and therefore generate more electricity